Factors Affecting Diversity and Distribution of Haemoparasites and Ectoparasites of Rodents and Shrews In Iringa District - Naomi Njogela; Jahashi Nzalawahe; Eliakunda Mafie (Universitas Airlangga, 2025)
Background: Rodents and shrews serve as a reservoirs and final hosts of various parasitic agents. Different factors are known to affect the diversity and distribution of the parasites harbored by them. Little is known on the factors affecting the diversity and distribution of parasites in rodents and shrews found at different elevations in Iringa District. Understanding these factors is crucial to comprehending how parasitic populations among small mammals spread. Purpose: This study aimed to investigate the factors associated with the diversity and distribution of ectoparasites and hemoparasites in rodents and shrews in Iringa. Method: A cross-sectional study was conducted in selected sites between March and June 2023. Rodents and shrews were captured using Sherman and wire traps, euthanized, and then their sex and species were identified. After that, ectoparasites, blood and tissue sample were collected and processed. The diversity and distribution of parasites at different sites were calculated using the Shannon-Wiener Index formula. Results: The overall prevalence of hemoparasites infection was 24.2 % (50/207), dominated by Anaplasma centrale (17.4%:36/207) followed by Plasmodium spp. (8.7%:18/207) and Anaplasma marginale (4.4%:9/207). A total of 713 ectoparasites belonging to five taxa were recovered from small mammals with an overall prevalence of 55.1% (114/207), dominated by mites; Echinolaelaps echidninus 46.4% (96/207), followed by lice; Polyplax spinulosa 16.9% (35/207), tick Hemaphysalis spp. 7.3% (15/207), and two flea taxa; Dinopsylla lypusus 2.9% (6/207) and Xenopsylla cheopis 1% (2/207). Conclusion: The high occurrence of Anaplasma centrale and Echinolaelaps echidninus suggests potential ecological and public health significance.